BOOK REVIEW: INTEGRATING INFORMATION AND COMMUNICATION TECHNOLOGIES IN ENGLISH FOR SPECIFIC PURPOSES - Hidayatulloh, Sibakhul Milad Malik (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
In the context of technological advancements permeating various domains, including language learning and teaching, educators find themselves compelled to adapt and remain abreast of the progressions in educational technology, regardless of their preparedness. The impact of Information and Communication Technology (ICT) on the methods of education has become increasingly evident over the past two decades. Hence, the provision of guidance is imperative to effectively assist teachers in managing the ICT classroom. The “Integrating Information and Communication Technologies in English for Specific Purposes” book aims to offer educators a comprehensive understanding of the integration of information and communication technology (ICT) with language learning and teaching. Furthermore, this publication offers an exploration of the utilization of various information and communication technology (ICT) platforms, applications, and websites to facilitate the advancement of English for Specific Purposes (ESP), English for Occupational Purposes (EOP), and English for Academic Purposes (EAP) in a straightforward manner.